New criteria for sustainable land use planning of metropolitan green infrastructures in the tropical Andes - LaRota-Aguilera, María José; Zapata-Caldas, Emmanuel; Buitrago-Bermúdez, Oscar; Marull, Joan (Springer, 2024)
Urbanization is rapidly increasing worldwide, with about 60% of the global population currently residing in cities and expected to reach 68% by 2050. In Latin America's tropical Andes region, managing these changes poses challenges, including biodiversity loss and vulnerability to climate change.